Effect of Radon and Lung Cancer Risk: A Narrative Literature Review - Elsesmita; Sabrina Ermayanti; Dewi Wahyu Fitrina (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Exposure to cigarette smoke has been known to be a major risk factor for lung cancer. Although smoking has long been considered the main cause of lung cancer, about 5 to 25% of lung cancer cases occur in non-smokers. Radon is said to be the second most important cause of lung cancer after smoking. Radon-222 is a chemical element in the form of a highly radioactive gas that comes from the decay of the parent radioactive element, uranium, which is found in the earth's crust. Inhaled radon gas can adhere to the mucosal lining of the airways and damage the airway epithelium. The process of ionizing radiation by alpha particles due to the decay of radioactive substances can cause mutations and chromosomal aberrations, severance of DNA double chains, and formation of reactive oxygen species. (ROS) that cause cell cycle changes, up-and down-regulation of cytokines, and increased production of proteins associated with cell cycle regulation and carcinogenesis. Research on radon and lung cancer has not been widely conducted in Indonesia. This literature review aims to describe radon and its effects on lung health.